The opinion of undergraduate medical students on current curriculum and teaching methodology of pharmacology in four medical colleges of India: a questionnaire based study - Saurabh, Manoj Kumar; Agrawal, Jitendra (International Journal of Basic & Clinical Pharmacology, 2016)
Background: The objective of current study was to obtain an opinion from 2nd professional year passed medical students on current curriculum, teaching methodology and importance of pharmacology subject and to identify the area of improvement. Methods: A set questionnaire was distributed among randomly distributed to 2nd year passed 100 undergraduate (UG) students to each of four medical colleges. They were instructed to tick out the best possible option of each question on the basis of their own perceptions. They are also asked to give suggestion to improve teaching and learning of pharmacology subject. Results: Out of the 400 students, only 387 responses of students were suitable for data analysis. The majority of students 99.22% (384) were unsatisfied with the practical teaching. Teachings of preparing and dispensing types of exercises were irrelevant in today’s clinical practice according to 87.78% of the students and were in favor of the deletion of such exercises from the curriculum. The analysis showed that 62.27% of the students were the opinion that animals should not be used in experimental pharmacology. More than half of the UGs (63%) supported the use of computer assisted learning. All of the students were interested in the inclusion of case, problem and multiple choice based question discussions in the regular teaching classes followed by quizzes (31.78%) and group discussions (14.47) while small number of students (1.03%) were interested in the conduction of seminars. Conclusion: There is an urgent need to reform the curriculum and practical teaching methods for fulfilling the objective of reading pharmacology.